THE PROCESS OF TALENT SELECTION IN THE PREPARATIONFOR THE EVENT OF TORCH RELAY OF THE ASIAN GAMES2018 - Austriana, Sarah; Priyanto, Priyanto (Journal of Indonesian Tourism and Policy Studies, 2018)
The journal is to show the readers about the process of determining talents of an event, which is the Asian Games Torch Relay that will be held from the 17th of july to 18th of August 2018 with seven routes of places to go to. Type of this research is qualitative and descriptive interpretive. Data were collected by interviewing officials of the company that selectted the talents for the event; and from the writer’s experience on helping in the process of it, as well as from the internal documents of the company. The result shows that in the process of finding the right talents needs to get through some steps which are, reading the manual, brainstorming, discussing, and then making sure if the candidates are willing to fill in for this event. The writer also concludes that how to decrease the candidates is by picking which ones fit to the circumstances best based on the bidder.